Hubungan Tingkat Kesejahteraan Masyarakat terhadap Jumlah Pekerja Migran Indonesia di Kab./Kota Tahun 2015-2019 - Fahrudin, Wawan; Susanti, Hera (UI Scholars Hub, 2022)
This study aims to analyze the effect of welfare levels on the number of Indonesian Migrant Workers (PMI) in districts/cities in 2015-2019. The variables in this study were measured using the Random Effect Model (REM) regression. The fact that has a high level of elasticity is the number of PMIs in the previous year, and in the previous 2 years, the area, and the total population. The variables in this study include: the level of community welfare as measured by the level of poverty, education indicators, and GRDP per capita with the control variables being population, area (land and sea), Java-outer Java, and district/city. The conclusion of the study is that the government has at least 2 (two) policy options, first, if you view the sending of PMI as a manifestation of poverty/poverty in the district/city, the government must issue a policy that focuses on poverty reduction programs in PMI enclaves, increasing GRDP per capita. and Expectations for Old Schools (HLS), especially in high-population districts, especially in Java, and having a small area, and policies that the government will take at least start from the previous 2 years. Second, if the government sees PMI delivery as an asset that must be handled, then the focus of government policy is focused on regions, especially districts with high poverty rates, low HLS, high population, in Java, with a narrow area.